Implementasi Jarimah Zina Di Aceh Dalam Perspektif Hadis - Syarifah Mudrika (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2023)
As a region that strives for the formal and material form of Islamic law, it is only natural that Aceh formulates a special regulation to replace the law called Qanun Aceh. The Aceh Qanun that specifically discusses the implementation of zina is Aceh Qanun No.6 of 2014 concerning Jinayat Law. Supposedly, as the Islamic Sharia area of Qanun Aceh related to zina in accordance with the hadiths of shoheh, in fact there are still hadith instructions that are not contained in the Aceh Qanun even though it is important to implement. This article is classified as literature research with a qualitative approach. The methodology used is a descriptive analysis study. The results of the study concluded that the implementation of jarimahh zina in Aceh that has not been in accordance with the hadith orders is stoning sanctions for muhsan adulterers, and exile sanctions for ghairu muhsan adulterers.